The Effect of Enterprise Risk Management on Financial Distress - Nur Khalizah Luthfiyanti; Lely Dahlia (Universitas Padjadjaran, 2020)
Lately, the retail industry has been suffering financial performance problem caused by some factors, such as the trade competition with online trading. Companies in the retail industry sector had to handle this risk to minimize further financial performance problem. The aim of this study is to determined the impact of the implementation of enterprise risk management in avoiding financial distress. This study used binary logistic regression for tool analysis. The sample of this study involved 21 retail companies listed on the Indonesia Stock Exchange from 2013 to 2017. The sample has been selected using a purposive random sampling method. Variable control, namely, liquidity, profitability, leverage, and company size, are included. The result of the study indicates that enterprise risk management implementation was found affecting financial distress